2021
DOI: 10.1007/s00192-021-04987-5
|View full text |Cite
|
Sign up to set email alerts
|

Intermediate term outcomes after transvaginal uterine-preserving surgery in women with uterovaginal prolapse

Abstract: Introduction and hypothesis There is growing interest in and performance of uterine-preserving prolapse repairs. We hypothesized that there would be no difference in pelvic organ prolapse (POP) recurrence 2 years following transvaginal uterosacral ligament hysteropexy (USLH) and sacrospinous ligament hysteropexy (SSLH). Methods This is a retrospective cohort study with a cross-sectional survey of women who underwent transvaginal uterine-preserving POP surgery from May 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…[8][9][10][11] Overall, there are little data published comparing the surgical outcomes and incidence of adverse events associated with the 2 types of vaginal hysteropexy. [12][13][14] Sacrospinous and uterosacral suspension procedures at the time of hysterectomy have been compared in the OPTIMAL Trial, 15 and over the long term, there are no differences in outcomes between the 2 suspension procedures. 16 Although it is tempting to extrapolate these data to hysteropexy techniques, it cannot be assumed that these procedures will perform similarly with uterine conservation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11] Overall, there are little data published comparing the surgical outcomes and incidence of adverse events associated with the 2 types of vaginal hysteropexy. [12][13][14] Sacrospinous and uterosacral suspension procedures at the time of hysterectomy have been compared in the OPTIMAL Trial, 15 and over the long term, there are no differences in outcomes between the 2 suspension procedures. 16 Although it is tempting to extrapolate these data to hysteropexy techniques, it cannot be assumed that these procedures will perform similarly with uterine conservation.…”
mentioning
confidence: 99%
“…Most of the data on vaginal hysteropexy are on the SSHP technique and have shown that SSHP has a similar cure rate when compared with vaginal hysterectomy with native tissue repair and may even be associated with fewer adverse events 8–11 . Overall, there are little data published comparing the surgical outcomes and incidence of adverse events associated with the 2 types of vaginal hysteropexy 12–14 . Sacrospinous and uterosacral suspension procedures at the time of hysterectomy have been compared in the OPTIMAL Trial, 15 and over the long term, there are no differences in outcomes between the 2 suspension procedures 16 .…”
mentioning
confidence: 99%